The Relationship Between Husbandal Support and the Adherence of Pregnant Women in the Second and Third Trimesters to Iron Tablet Consumption at the Shaqi Seyegan Clinic in 2023 - Ratu Ainan Sungkar; Nurul Soimah (Blantika: Multidisciplinary Journal, 2026)
Compliance of pregnant women in consuming Fe tablets is one of the important efforts to prevent anemia during pregnancy. This study aims to determine the relationship between husband support and the compliance of pregnant women in the second and third trimesters in consuming Fe tablets at the Shaqi Seyegan Clinic in 2023. This study uses a quantitative design with a cross-sectional approach. The population in this study comprises pregnant women in the second and third trimesters who underwent antenatal care at the Shaqi Seyegan Clinic in 2023. Sampling was carried out in accordance with predetermined inclusion criteria. Data collection was conducted using questionnaires regarding husband support and compliance with Fe tablet consumption. The data obtained were analyzed using univariate and bivariate analyses to determine the relationship between husband support and pregnant women's compliance in consuming Fe tablets. The results of the study show that husband support plays an important role in the compliance of pregnant women in consuming Fe tablets. Pregnant women who receive good support from their husbands tend to be more compliant in taking Fe tablets compared to those who receive less support. Thus, it can be concluded that there is a significant relationship between husband support and the compliance of pregnant women in the second and third trimesters in consuming Fe tablets at the Shaqi Seyegan Clinic in 2023. Husband support needs to be strengthened through family education so that pregnant women's compliance in consuming Fe tablets can be further optimized.